2015
DOI: 10.1007/s11356-015-5294-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of methyl orange dye biotreatment by a novel isolated strain, Aeromonas veronii GRI, by SPB1 biosurfactant addition

Abstract: Aeromonas veronii GRI (KF964486), isolated from acclimated textile effluent after selective enrichment on azo dye, was assessed for methyl orange biodegradation potency. Results suggested the potential of this bacterium for use in effective treatment of azo-dye-contaminated wastewaters under static conditions at neutral and alkaline pH value, characteristic of typical textile effluents. The strain could tolerate higher doses of dyes as it was able to decolorize up to 1000 mg/l. When used as microbial surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 79 publications
(104 reference statements)
2
19
0
Order By: Relevance
“…The most important observation is the tolerance of the bacterial isolate to high doses (1000 mg L −1 ) of MO for a long period (144 h). This result is in agreement with those of Mnif et al The reported concentration (1000 mg L −1 ) is higher than those reported by others . In contrary, Shah et al observed the inhibitory effect of MO on growth of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 92%
“…The most important observation is the tolerance of the bacterial isolate to high doses (1000 mg L −1 ) of MO for a long period (144 h). This result is in agreement with those of Mnif et al The reported concentration (1000 mg L −1 ) is higher than those reported by others . In contrary, Shah et al observed the inhibitory effect of MO on growth of Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Mnif et al investigated the MO dye bio‐treatment efficiency of Aeromonas veronii GRI and reported that this strain could tolerate a higher concentration of dye since it could efficiently decolourize up to 1000 mg/L in mineral salt medium (MSM) after 24 h incubation. Ayed et al reported a 92 % degradation of MO (750 mg/L) within 48 h at pH 7 and 30 °C in MSM containing glucose and yeast extract.…”
Section: Resultsmentioning
confidence: 99%
“…A typical textile industrial wastewater contains methyl orange (MO) dye concentration in the range of 50–150 mg/L . Recently, numerous studies related to bio‐decolourization of MO by bacteria and fungi have been reported . However, the effect of operational parameters (like nutrient composition, pH, and temperature) on the treatment process is yet to be explored elaborately.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, on the 3 rd day, decolorization was recorded with 50% efficiency, which then changed to 86% on the 6 th day of experiment for VTK024. The divergence in the decolorization efficiency was caused by the variation in the selectivity of bacterial isolates; the composition and complexity of chemical dyes, specifically relating to the type; and the placement of substituents (para and ortho) in the aromatic rings and the interaction with R!N=N!R bond as mentioned by various researchers (Chaieb et al, 2016;Jha et al, 2016;Mnif et al, 2016). A majority of the bacteriological genera, i.e., Enterococcus, Staphylococcus, Pseudomonas, Proteus, and Bacillus, which were tested in this study, have been published earlier (Chaieb et al, 2016;Neifar et al, 2016).…”
Section: Dye Decolorization Assaymentioning
confidence: 99%
“…such as Proteus vulgaris NCIM 2027 as a dye-decolorizing agent for textile dye degradation has been investigated previously (Saratale et al, 2011). These studies revealed the occurrence of different microbial genera, which were characterized as (Mnif et al, 2016;Ng et al, 2014). However, bacterial isolates, i.e.,…”
Section: Dye Decolorization Assaymentioning
confidence: 99%